2015 24th IEEE International Symposium on Robot and Human Interactive Communication (RO-MAN) 2015
DOI: 10.1109/roman.2015.7333594
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of different roles for domestic social robots

Abstract: Robotics researchers foresee that robots will become ubiquitous in our natural environments, such as our homes. For a successful diffusion of social robots, it is important to study the user acceptance of such robots. In an online survey, we have investigated the acceptance of three different possible roles for domestic social robots and the preferred appearance. The results show that, although most people prefer a humanoid robot for domestic purposes, the role for which a social robot is build affects the cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Additionally, the category of AI produced highly diverse drawings, ranging from fullyembodied robots to abstract networks. These findings support earlier research suggesting that a robot's appearance should match its intended application domain (Goetz, Kiesler, & Powers, 2003;Graaf & Ben Allouch, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, the category of AI produced highly diverse drawings, ranging from fullyembodied robots to abstract networks. These findings support earlier research suggesting that a robot's appearance should match its intended application domain (Goetz, Kiesler, & Powers, 2003;Graaf & Ben Allouch, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…This may indicate that people's expectations for generic and household robots include some humanoid features, but perhaps not as many as a near human-looking android. A similar tension was identified in the study by de Graaf and Ben Allouch (2015), which found that although people favored a humanoid appearance for a household robot, they expressed that robots should be easily distinguishable from humans. Thus, robot developers will want to consider the level of human-likeness of robot appearance in their designs, which might be dependent on application domain.…”
Section: Discussionsupporting
confidence: 65%
“…However, the stimuli consisted of silhouettes representing only humanoid robots. From our previous work [18], [20] we have learned that people's evaluations of robots differentiate between embodiments or appearances. Therefore, replication of our study is necessary with different robotic appearances.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the adoption of robots have also shown that a robot's appearance has a positive impact on user evaluation when it matches the task that the robot is designed to perform (Smith et al, 2016). De Graaf and Allouch (2015) showed that robots with zoomorphic appearances (i.e., having appearances resembling actual animals) are considered more suitable for companion roles, whereas those with utilitarian appearances (i.e., having appearances of machines used for specific functions) are more suitable for butler roles. These results imply that an AI robot's appearance and the type of benefit they intend to provide needs to be compatible for the ease of their adoption.…”
Section: Literature Reviewmentioning
confidence: 99%